Evaluasi Pelaksanaan Sistem Zonasi pada Penerimaan Peserta Didik Baru Provinsi Kepulauan Riau Tahun 2023 : Studi Kasus SMA Negeri 3 Tanjungpinang - Nadia Tika Adisti; Jamhur Poti; Firman Firman (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
New Student Admission in the zoning system has been carried out since 2017. However, as long as this zoning system is in effect, it has not been able to guarantee an equal distribution of the number of students accepted in each school, because there is still one school that receives the number of students not up to the predetermined capacity plan. The purpose of this study is to determine the results of the implementation of the zoning system in the New Student Admission in 2023 in Tanjungpinang City. The research used is a qualitative method. The theory used is the evaluation indicators according to Dunn (2000). The results showed that the implementation of the zoning system that had been implemented in 2023 in the effectiveness dimension showed that the implementation of PPDB in the zoning system was not carried out optimally in accordance with the rules stated in the Technical Guidelines. The efficiency dimension shows that the agency has made a number of efforts to be able to achieve equal distribution of capacity, but the results of the implementation that occur in the field cannot be considered efficient because the community itself still adheres to the understanding of favorite schools or hereditary schools. The adequacy dimension shows that the facilities and infrastructure in Tanjungpinang City have not been carried out evenly. The equalization dimension shows that the implementation of the zoning system in 2023 cannot guarantee the equalization of the capacity plan received in each school.